Monocyte at diagnosis as a prognosis biomarker in tuberculosis patients with anemia - Luo, Mengxing; Zou, Xin; Zeng, Qibing; Wu, Yaxing; Yang, Hua; Qin, Lianhua; Zheng, Ruijuan; Yu, Fangyou; Hu, Yang; Liu, Zhonghua (Frontiers in Medicine, 2023)
Abstract Background: Anemia leads to lower cure rate and poor prognosis of tuberculosis patients. Effective predictors for tuberculosis with anemia(A-TB) are urgently needed. Monocyte has been proved to be a prognostic biomarker of many lung diseases. Whether monocyte that the predominant innate immune cell as early defense against tuberculosis can predict A-TB is not known. Methods: Data for non-treated A-TB patients in Shanghai Pulmonary Hospital were retrospectively collected and analyzed. Logistics regression analysis was used to study the correlation between peripheral blood cells and treatment outcome. The ROC curve was used to determine the cut-off value. We estimated 12-month prognosis using Kaplan-Meier techniques. The Cox proportional hazards model was used for the univariate and multivariate analyses to analyze the predictors of poor prognosis of A-TB. Results: Of 181 patients analyzed, 94 were cured and 87 non-cured. Logistic regression analysis identified MONO was an independent immune-related risk factor for the prognosis of A-TB(OR:7.624,95%CI:1.787-32.533,P=0.006). The ROC curve analysis proved that the most discriminative cut-off value of MONO was 0.535×10^9/L. K-M analysis demonstrated that the cumulative cure rates of A-TB were signifcantly higher in A-TB with MONO<0.535×10^9/L (69.62%) than that in those with MONO≥0.535×10^9/L (38.24%)(Log-rank,²=16.53,P<0.0001). On univariate and multivariable analysis, MONO was an independent predictor of poor prognosis in A-TB. Similarly, MONO was also an independent predictor of poor pulmonary cavity closure in A-TB (HR:2.732,95%CI:1.110-6.728,P=0.029). Conclusions: In A-TB patients, elevated monocyte was associated with poor prognosis and poor cavity pulmonary closure. Monocyte may provide a simple and inexpensive prognostic biomarker in A-TB.